The effect of heat treatment on crystal structure and thermodynamic properties of Cu-Al-Ni shape memory alloy - Mohammed, Safar Saeed; Karim, Ayoub Sabir; Qadir, Rezhaw Abdalla; Koek, Mediha; Dagdelen, Fethi; Wsw, Avin Faisal; Othman, Abdulla Maghdid (Springer, 2025)
This study investigates the effects of heat treatment on the properties of Cu-Al-Ni shape memory alloy (SMA). The Cu-Al-Ni alloy was synthesized using an induction melting furnace, and followed by quenching (hardening) at three different temperatures (673 K, 873 K, and 1073 K) using an electrical furnace for an hour. The effects of heat treatment on thermal properties, transformation temperatures, crystal structure, microhardness, and microstructure, were analyzed using differential scanning calorimetry (DSC), X-ray diffraction (XRD), Vickers hardness tests, and scanning electron microscopy (SEM). Results indicated that heat treatment increased transformation temperatures and enhanced thermal stability, with changes in enthalpy and entropy. XRD analysis revealed a reduction in phase intensity and grain size with increasing treatment temperature, correlating with increased hardness due to grain boundary effects. SEM micrographs confirmed the presence of the martensite phase at room temperature. These findings demonstrate that heat treatment improves the material's performance, making it more suitable for high-temperature applications in industries such as aerospace and automotive.
Keywords: Heat treatment; Hardening; HTSMAs; Cu-Al-Ni; Ternary shape memory alloy